PERANCANGAN E-MANDEH DI KAWASAN WISATA MANDEH MENGGUNAKAN FRAMEWORK CODEIGNITER BERBASIS WEB - Rozi Gustian; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Tourism is one of human needs. By doing tours, humans can momentarily unwind, get tired and relieve stress, and for a moment forget the problems experienced both at home and in the office. Mandeh Tourism Area is one of the most crowded tourist spots for visitors to go to, tourists have to order bots by way of face to face. The desire of customers to get good and fast service makes business people to be able to improve services as much as possible. Applications that are built using CodeIgniter framework, make the system look more neat, organized and high-performance. The programming languages used are HTML and PHP. The system appearance is interesting because it uses bootstrap which is combined with CSS. Applications that are built using the waterfall method. There are several stages that exist in this method, including analysis of system requirements, design interface consists of home page, login page, register page, admin page and the order page is paid. Keywords: Tourism Bot Business, framework codeigniter